FACTORS INFLUENCING TAX COMPLIANCE IN INDONESIA - Apran Kurniawan; Revi Novayanthi Br Meliala; Fernandus Roni Febrianto (Kesatuan Press, 2023)
This study aims to look at several factors like awareness, knowledge, obstacles, and sanctions, as well as tax regulations impacting taxpayer compliance. There is an assumption that tax compliance in Indonesia is still in the low category, which causes state revenues in the tax sector not to meet expectations. This study uses the literature review method, where the results concluded that awareness, knowledge, obstacles, sanctions, and the existence of tax regulation have an indication or influence to increase tax compliance in Indonesia. The study provides knowledge about the current conditions regarding tax compliance in Indonesia based on existing factors, and new information related to the recent tax regulation in the pandemic 2022.